1979
DOI: 10.2355/tetsutohagane1955.65.3_391
|View full text |Cite
|
Sign up to set email alerts
|

Eutectic Conjugation in Fe-Mn-S System

Abstract: The conjugation of , and in the Fe-Mn-S ternary system with up to 4% of manganese in iron phase, was investigated as the first approach to understand kinetics of sulfide formation in steel, and the compositions of all phases were determined in the temperature range from 670•Ž to 1500•Ž.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A number of studies have shown that secretion of catecholamines and proenkephalin A-derived peptides from adrenal medullary cells can be increased by nicotinic receptor stimulation with acetylcholine (ACh) and depolarizing agents such as potassium (K+), barium (Ba2+) and veratridine (VT) (Livett et al, 1981;Kilpatrick et al, 1981;Viveros et al, 1979;Ito et al, 1979). Electrophysiological and biochemical studies have provided evidence that an increase in cytoplasmic calcium is a necessary step in the secretory process (Douglas et al, 1967;Douglas, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that secretion of catecholamines and proenkephalin A-derived peptides from adrenal medullary cells can be increased by nicotinic receptor stimulation with acetylcholine (ACh) and depolarizing agents such as potassium (K+), barium (Ba2+) and veratridine (VT) (Livett et al, 1981;Kilpatrick et al, 1981;Viveros et al, 1979;Ito et al, 1979). Electrophysiological and biochemical studies have provided evidence that an increase in cytoplasmic calcium is a necessary step in the secretory process (Douglas et al, 1967;Douglas, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…The equilibrium constant for reaction (4) can be expressed as: and further as: (6) temperatures as well as the basicities. The work of Tranell et.…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary to investigate in more detail the activity behaviour of reducible oxides in carbon containing slags to minimize steel reoxidation. However, studies on carbon containing slags have focused mainly on solubility and stable forms of carbon in slag [2][3][4][5][6]. To date there have been no reports on the effect of carbon in slag on the activities of Fe.O and MnO.…”
Section: Introductionmentioning
confidence: 99%